NIAT APARATUR SIPIL NEGARA (ASN) UNTUK MELAKUKAN WHISTLE-BLOWING: PENGARUH KOMITMEN ORGANISASI, PERSONAL COST, DAN REWARD - Agustina Putri Pertiwi Widyanto; Firma Sulistiyowati (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2020)
This study investigates the influence of organizational commitment and personal cost on civil servant’s intention to do whistle-blowing with reward as moderating variable. To collect the data, this study uses survey method. The 64 civil servants at BPK Lampung Office become respondents of this study who are chosen through purposive sampling method. The Partial Least Square is used to analyze the quantitative data. The findings of the study indicate that organizational commitment gives influence on civil servants to do whistle-blowing. Personal cost does not impact on civil servants to do whistle-blowing. Reward cannot enforce or lessen the influence of organizational commitment and personal cost on civil servants to do whistle-blowing.